Intestinal anastomoses in small children: is there a higher risk? - Weih, Sandra; Jung, Ve; Romero, Philipp; Chmelnik, Martin; Holland-Cunz, Stefan (Journal of pediatric gastroenterology and nutrition, 2010)
The aim of the retrospective study was to evaluate complications and outcome of children in whom an intestinal anastomosis had been performed at age younger than 1 year.